Effect of fermentation time on butanol and ethanol production from palm mill oil effluent by clostridium acetobutylicum - Muhammad Zaidi, Othman (2010)
Biofuels production through fermentation from renewable waste has been put more to focus in mid 20th century till now. Main focus of the research is to determine optimum fermentation time to obtain maximum concentration of butanol and ethanol via ABE fermentation. The ABE fermentation is a two phase chemical production which is from acidogenesis into solventogenesis. The fermentation is caused by clostridia bacteria and in this case of study is Clostridium acetobutylicum pattered NCIMB 13357. The main substrate for nutrient in this study is Palm Oil Mill Effluent (POME) which freshly taken from Lepar Hilir, Pahang. Through the research, POME was found to contain majorly of pentose and carbohydrate substance such as galactose, glucose, fructose, sucrose and lactose. The research parameter is fermentation time at 72, 80, 48 and 60 hours. The experiments start from medium preparation, cultivation of bacteria, inoculation, fermentation and lastly analysis of product. All standard solution is made in order to standardize the reading of concentration of product and substance analyzed. The condition for bacteria environment is set to anaerobic and optimum pH at 5.8, temperature at 37 ⁰C and agitation speed is set at 200 rpm along ABE fermentation. Final result shown that at fermentation time of 40 hours, the maximum value of 0.07 g/L of butanol was produced, while for ethanol is 83.499 g/L at 20 hour fermentation time. POME is encouragingly valid for use as fermentation media as it contain many utilizable substrates for Clostridium acetobutylicum.